Improvements in Compliance with Medical Force Protection Measures by Simplification of the Anti-Malarial Chemoprophylaxis Regime. Issue 2 (1st June 2011) - Sellers, Emma; Ross, DA; Green, AD
Abstract : Objectives: Medical Force Protection (MFP) is important in keeping service personnel "fit to fight." It is particularly important for overseas deployment, where personnel are exposed to a range of infectious diseases. We report a full audit cycle assessing compliance with medical force protection measures, on an exercise in Belize. Methods: An anonymous questionnaire was administered to personnel four weeks after returning from an Infantry Overseas Training Exercise (OTX) in Belize in two successive years (OTX 1& 2). Results: Compliance with physical MFP measures (mosquito nets, insecticide soak of kit and personal insect repellent usage) was excellent on both exercises. Antimalarial chemoprophylaxis compliance with a regime of weekly chloroquine and daily proguanil was poor (30%) during OTX 1. Revision of the regime to weekly chloroquine alone following review of anti-malarial policies increased compliance on OTX 2 to 67%. Conclusion: Simplification of dosage regimes, consistency of information provided between different medical briefs and emphasis of the threat from malaria in Belize significantly improved compliance with antimalarial chemoprophylaxis.